Review: German Literary Culture in the Twelfth and Thirteenth Centuries by Nigel F. Palmer - Kauffmann, M (Society for the Study of Mediaeval Languages and Literature, 1995)
Nigel F, Palmer, German Literary Culture in the Twelfth and Thirteenth Centuries (Oxford:Clarendon Press, 1993). 24 pps 6 plates. ISBN 0-19-952260-x. £6.50.